Polycrystalline Compound of Co2+-doped Zn2SnO4: Structural and Photoluminescent Properties - Alvarenga,T. L. (2022)
Abstract In this work, Zn2SnO4:Co2+ (0.1%) was obtained through a solid-state reaction at high temperature using ZnO, SnO2, and CoCO3. The sample was investigated using X-ray diffraction, X-ray fluorescence, scanning electron microscopy, and photoluminescence spectroscopy. Rietveld refinements of the X-ray diffraction data showed two crystalline phases, Zn2SnO4 and SnO2, with proportions of 97.24% and 2.76%, respectively, while Zn and Sn atoms were observed by X-ray fluorescence. Scanning electron microscopy images showed the polycrystalline nature of the material. Photoluminescence spectroscopy showed two emission bands in the red and near-infrared regions, with the broader and more intense band having a barycenter at 694 nm. The intensity of the emission changed with the excitation wavelength, whereas the barycenter remained unchanged. The intensity, shape, and position of the bands, as well as the calculated crystal field parameters, indicate the insertion of Co2+ ions in the tetrahedral sites of the Zn2SnO4 material.